IMPLEMENTASI PENDIDIKAN KARAKTER BERDASARKAN SEBELAS PRINSIP PENDIDIKAN KARAKTER YANG EFEKTIF (Studi pada Sekolah Menengah Pertama Wijaya Putra) - Syaiful Azmi; Indra Prasetyo; Woro Utari (Jurnal Manajerial Bisnis, 2023)
This study describes the implementation of character education in SMP Wijaya Putra based on eleven principles of effective character education by Lickona and its supporting and inhibiting factors. Data obtained from questionnaires and interviews. The selected informants were the school principal, vice-principal, homeroom teacher, and several students. The analysis shows SMP Wijaya Putra applies the eleven principles of effective character education by fulfilling each indicator in each principle. Based on the analysis, it is obtained several supporting factors, including: stakeholder support, formulation of agreed character goals in the form of six pillars, various programs and activities that integrate character education, school is an ethical community, meaningful curriculum and challenge, involvement of student guardians and the community in the application of character education, and assessment of the student character education achievement. In addition to supporting factors, several inhibiting factors are obtained which, if minimized, can enhance the implementation of character education in SMP Wijaya Putra. The inhibiting factors include: an informal character education effectiveness survey; cultural, climate and school function assessments as ethical learning communities are not optimal; teacher and staff reflection as informal character educators; and assessment of student understanding of ethical values ​​and behaviors aspects have not been covered.